CORRELATION BETWEEN KNOWLEDGE, LEARNINGACHIEVEMENT AND PERSONAL HYGIENE WITH INCIDENCE OF HELMINTHIASIS ON ELEMENTARY STUDENT - BESTARI, ROCHMADINA SUCI; AISYAH, RIANDINI; TOLIBIN, RESTU TRIWULANDANI; NURHAYANI; KUSUMANINGRUM, TANJUNG ANITASARI INDAH; NAJMII, MUHAMMAD FIROOS ‘ALLAM (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2026)
Background: Helminthiasis is a health problem in Indonesia that affects many elementary school children. The effects of worms in children can be malnutrition, anemia and decreased academic achievement. The government has carried out control of worm diseases by providing deworming drugs every 6 months. However, the effectiveness of this program has not been widely studied, the incidence of worms in each region is not widely known, including the risk factors that influence it. Objective: This study aims to determine the correlation between knowledge, learning achievement and personal hygiene with the incidence of helminthiasis in students at Selokaton Karanganyar Elementary School II. Method: The method used is a cross-sectional study, with total sampling. Students were asked to fill out a knowledge and personal hygiene questionnaire, then collect feces. Learning achievement were obtained from final mark of the semester. Feces examination using direct smear and 2% eosin staining. Analysis used binary logistic regression test and Mann-Whitney U test. Result: The results of this study were that students who were positive for helminthiasis were 16%, hookworm infections were the highest burden (10/16), followed by ascariasis an enterobiasis. There was no significant correlation between knowledge, learning achievement and personal hygiene with the incidence of helminthiasis (p>0.05). Conclusion: The conclusion of this study is that there is no significant correlation between knowledge, learning achievement and personal hygiene with the incidence of the incidence of helminthiasis (p>0.05).